AN ANALYSIS ON CODE-SWITCHING IN THE NOVEL ‘NY OVER HEELS’ - Vanisha Nindya Putri; Jismulatif Jismulatif; Dahnilsyah Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study discusses the phenomenon of code switching in a novel titled NY Over Heels written by Dy Lunaly (2003). The researcher used a study document as the way to collect the data and The research design of this research was a library study with qualitative research. A Study document is getting the data about a case or variable from note, book, magazine, novel, etc (Arikunto, 1990). The key instrument of this research is the researcher herself. Based on the research that had been done, the research comes to some conclusions. Firstly, As the result, there are 87 data that have been found by the researcher. The data showed that Emblematic or tag switching is about 8.04% from 87 data. Intra-sentential is about 37.93% from 87 data. Inter-sentential is about 54.02% from 87 data. The dominant type of code switching found in the novel is inter-sentential from 28 chapters. Secondly, Besides the type of code switching, it was found that the reasons why the characters in the novel use code switching. From seven reasons that Hoffman (1991) states, there are six reasons have been found from the 87 data code switching from the novel that researcher classify. The data showed that expressing group identity is 28 times or 32.18%. Talking about particular topic is 19 times or 21.83%. Emphatic is 12 times or 13.79%. The repetition used for clarification is 5 times or 5.74%. Intention of clarifying the speech content for interlocutor is 1 time or 1.14%. And the last Interjection is 22 times or 25.28%. In this section of the reason of code-switching is the highest calculation has found is expressing group identity is 28 times from 28 chapters.Key Word: Code-Switching, The Novel Dy Lunaly.